2021
DOI: 10.3389/fbioe.2021.762209
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study Assessing the Impact of Intrathecal Administration of Variants AAV-PHP.B and AAV-PHP.eB on Brain Transduction in Adult Rhesus Macaques

Abstract: Adeno-associated virus (AAV) vectors are increasingly used as an effective and safe approach to deliver genetic material to the central nervous system (CNS). The AAV9-derived variants, AAV-PHP. B and AAV-PHP.eB, reportedly broadly transduce cells throughout the CNS compared to the original serotype 9, AAV9. As non-human primate data are scarce, we here evaluated the CNS transduction efficiencies after lumbar intrathecal bolus delivery of identical doses of either AAV-PHP. B:CAG-EGFP or AAV-PHP. eB:CAG-EGFP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…2). Expression was especially low in subcortical structures, as reported previously [41][42][43][44][45] .…”
Section: Characterization In Newborn Macaques and Infant Green Monkey...supporting
confidence: 87%
See 1 more Smart Citation
“…2). Expression was especially low in subcortical structures, as reported previously [41][42][43][44][45] .…”
Section: Characterization In Newborn Macaques and Infant Green Monkey...supporting
confidence: 87%
“…In addition to CAP-Mac's utility as a tool to study the primate brain, it is also a compelling potential delivery vehicle for genetic medicine in humans. It provides an unprecedented opportunity to deepen our understanding of pharmacodynamics in Old World primate models 30,83,84 and its broad and uniform distribution throughout the CNS opens access to subcortical and midbrain regions for neuroscience researchers, currently difficult in NHPs [41][42][43][44][45] . Additionally, CAP-Mac's enhanced transduction of cultured human neurons supports its potential as a gene-delivery vehicle in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection can also be targeted towards specific cell types aiming in a more limited biodistribution and fewer off‐target side effects. For such cases we suggest the employment of engineered tissue‐selective viral capsids (Arotcarena et al., 2021; Barnes et al., 2019) and/or the use of tissue‐specific promoters that provide cell‐specific expression (Kagiava, Karaiskos, et al., 2021; Kagiava et al., 2018; Kagiava et al., 2019; Kagiava, Richter, et al., 2021; Kagiava et al., 2016; Schiza et al., 2019).…”
Section: Commentarymentioning
confidence: 99%
“…Moreover, GFP can be detected in cerebellar Purkinje cells, the medulla, and discrete nuclei after intracisternal and intralumbar injection of rAAV9-GFP in 5-day-old pigs ( Bevan et al, 2011 ). Studies showed that rAAV-PHP.eB was superior to rAAV9 in brain transduction rate after intracisternal injection in adult rats and after intrathecal injections in non-human primates ( Arotcarena et al, 2021 ; Chatterjee et al, 2022 ). However, the PHP.eB variant raises concerns about their species and strain specificity as discussed above.…”
Section: Delivery Into the Csfmentioning
confidence: 99%